Studi Diagnostik Profil Mental Toughness dan Kecemasan Bertanding Atlet Petanque Bk Porprov Garut 2025: Studi Diagnostik Profil Mental Toughness Dan Kecemasan Bertanding Atlet Petanque Bk Porprov Garut 2025 - Vina Vauziah; Asep Angga Permadi; Ani Kurniawati (Jurnal Porkes, 2026)
Competition anxiety is a major psychological challenge often experienced by young athletes, especially in precision sports such as petanque, which require high levels of concentration and emotional stability. The inability to manage anxiety can interfere with performance, while mental toughness acts as a protective factor in dealing with competitive pressure. This study aims to diagnose the mental toughness and competition anxiety profiles of BK Porprov Garut 2025 petanque athletes and analyze the relationship between these two variables. The approach used is quantitative with a descriptive-correlational method. The research sample consisted of 16 athletes selected through purposive sampling. The research instruments were mental toughness (14 items) and competition anxiety (15 items) questionnaires compiled based on the Likert scale. Data analysis used descriptive statistics and Pearson's Product Moment correlation test. The results showed that most athletes had moderate mental toughness (43.8%) and high competition anxiety (56.7%). The correlation test yielded a value of r = -0.692 with a significance of 0.001, which means that there is a strong and significant negative relationship between mental toughness and competition anxiety. The conclusion of this study confirms that increased mental toughness is associated with a decrease in competitive anxiety in adolescent athletes.